1999
DOI: 10.1046/j.1365-2249.1999.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the mechanism of cytolysis by tumour-infiltrating lymphocytes

Abstract: SUMMARYIn order to determine the mechanism of tumour destruction by tumour-infiltrating lymphocytes (TIL), we examined the ability of both CD4 þ and CD8 þ effector TIL, and TIL clones, to manifest granzymemediated and Fas-mediated destruction of tumour targets. In many in vitro studies TIL have been shown to manifest anti-tumour reactivity, yet many tumours escape immunological destruction. To investigate the role of Fas expression and the concomitant sensitivity to the inducibility of apoptotic death, we deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 54 publications
2
21
0
Order By: Relevance
“…Studies have shown that CD4 ϩ T cells that infiltrate tumors contain perforin granules and have the potential to kill by Fas/FasL system (36,37). Because class II Ags are expressed in different solid malignancies including melanoma (38,39), CD4…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CD4 ϩ T cells that infiltrate tumors contain perforin granules and have the potential to kill by Fas/FasL system (36,37). Because class II Ags are expressed in different solid malignancies including melanoma (38,39), CD4…”
Section: Discussionmentioning
confidence: 99%
“…4). 6 The different MITF isoforms are transcribed from different promoters, with isoform-specific 5 ¶ exons spliced onto common 3 ¶ exons (25), and the respective isoforms are, therefore, subject to divergent transcriptional controls. Significant suppression of MITF-M expression by MEK inhibitors would seem unlikely to be correlated with increased MITF-M function.…”
Section: Control Of Melanocytic Antigen Gene Expression Mol Cancer Rementioning
confidence: 99%
“…The products of many of these genes are localized in the melanosome, and some are directly linked to melanin synthesis (1)(2)(3). Importantly, with respect to immunotherapy, several melanocytic gene products have been directly shown to function as target antigens for CTLs (4)(5)(6)(7)(8)(9). Loss of such antigen expression by target melanoma cells is thus a mechanism for escape from immune recognition (10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…15 In Fas-sensitive tumor cells, CTLs can induce tumor cell apoptosis by FasL, which is one of the mechanisms by which CTLs kill tumor cells. 16 It is not clear whether the activation of Fas signaling initiated by FasL on CTLs affects apoptosis-resistant tumor cells. We questioned whether CTLs could improve tumor escape via the activation of Fas-induced non-apoptotic signaling in Fas-resistant tumor cells.…”
Section: Introductionmentioning
confidence: 99%